Factors Affecting the Use of Information and Communication Technology (ICT) for Agricultural Information among Smallholder Farmers in Chitwan and Lamjung Districts of Nepal - Mishra, Binayak Prakash; Sigdel, Udit Prakash; Devkota, Durga; Devkota, Kedar (Journal of the Institute of Agriculture and Animal Science, 2023)
ICT have power to enrich smallholder farmers to the agriculture information and to promote sustainable agricultural development, particularly in the developing countries. An investigation was done during 2019 to know the about the factors affecting the use of ICT with respect to agriculture information by smallholder farmers in Chitwan and Lamjung districts of Nepal. The study areas were selected purposely whereas a total of 120 smallholder farmers (60 farmers from each district) were selected randomly. Pre-tested semi structured interview schedule was used for household survey, whereas respective checklists were used for Focus Group Discussion (FGD) and Key Informant Interview (KII) to gather primary data. Findings from the logit model revealed that use of ICT increases with farming experience, and contact with extension worker, and decreases with age, education and net worth. Hence, it was well revealed that ICT based agriculture information delivery is effective to the young smallholder farmers having regular contact with extension worker and having longer farming experience at the present scenario.